Illegal Under the Laws of All Nations? The Courts of Haiti and the Suppression of the Atlantic Trade in African Captives. (23rd April 2019) - Walker, Andrew
Abstract : In 1816, the mostly-American crew of a slaving brig bound from Cuba staged a mutiny before reaching West Africa, and then sailed on (without a captive cargo) to the antislavery republic of Haiti. Their voyage culminated in a remarkable prize case before the admiralty court at Port-au-Prince. The sailors claimed indignation at the "diabolical" slave trade, hoping to win profits from the condemnation of the vessel and to avoid future prosecution for enlisting in a slaving voyage that was illegal under U.S. federal law. Haitian prosecutors invoked the agreements of the Congress of Vienna, arguing that the trade had been prohibited by the laws of nations. It fell to the admiralty court to reconcile such aspirational claims with Haiti's ongoing struggle for political survival. The brig's journey between the United States, Cuba, Spanish Florida, Cape Verde, and finally Haiti reveals the ways in which slave traders calculated the relative risks of legal penalties against the possible gains from the trade. The records of the adjudication of the case show how Haitian officials developed their own legal strategies for the suppression of the trade, laying the foundations for an escalating campaign to police slaving traffic off of their shores.